Dual‐polarity pulse processing and analysis for charge‐loss correction in cadmium–zinc–telluride pixel detectors. (27th June 2018) - Abbene, Leonardo; Gerardi, Gaetano; Principato, Fabio; Bettelli, Manuele; Seller, Paul; Veale, Matthew C.; Fox, Oliver; Sawhney, Kawal; Zambelli, Nicola; Benassi, Giacomo; Zappettini, Andrea
Abstract : Charge losses at the inter‐pixel gap are typical drawbacks in cadmium–zinc–telluride pixel detectors. New techniques, based on the time coincidence analysis of both the positive and negative pulses, were applied to correct the charge losses near the inter‐pixel region. Abstract : Charge losses at the inter‐pixel gap are typical drawbacks in cadmium–zinc–telluride (CZT) pixel detectors. In this work, an original technique able to correct charge losses occurring after the application of charge‐sharing addition (CSA) is presented. The method, exploiting the strong relation between the energy after CSA and the beam position at the inter‐pixel gap, allows the recovery of charge losses and improvements in energy resolution. Sub‐millimetre CZT pixel detectors were investigated with both uncollimated radiation sources and collimated synchrotron X‐rays, at energies below and above the K ‐shell absorption energy of the CZT material. The detectors are DC coupled to fast and low‐noise charge‐sensitive preamplifiers (PIXIE ASIC) and followed by a 16‐channel digital readout electronics, performing multi‐parameter analysis (event arrival time, pulse shape, pulse height). Induced‐charge pulses with negative polarity were also observed in the waveforms from the charge‐sensitive preamplifiers (CSPs) at energies >60 keV. The shape and the height of these pulses were analysed, and their role in the mitigation of charge losses in CZT pixel detectors. These activities are in the framework of an international collaboration on the development of energy‐resolved photon‐counting systems for spectroscopic X‐ray imaging (5–140 keV).